Sugarcane spirit market share simulation: an application of conjoint analysis - Carneiro,João de Deus Souza (2012)
This study evaluated the influence of packaging and labeling attributes of sugarcane spirit on consumers' behavior by applying the results of conjoint analysis in sugarcane spirit market share simulation. Firstly, a conjoint analysis was performed aiming to estimate the part-worths of each consumer for some sugarcane spirit packaging and labeling attributes. These part-worths were used in the market share simulation using the maximum utility model. It was observed that some packaging and labeling attributes affected consumer's purchase intention and that most consumers showed a similar preference pattern regarding these attributes. These consumers showed preference for the Seleta brand, which was bottled in 700 mL clear glass bottles with a metal screw cap that bore a label illustration unrelated to sugarcane spirit production process and had the information "aged 36 months in oak barrels". This study also showed that conjoint analysis and the use of its results in the market share simulation proved important tools to better understand consumer behavior towards intention to purchase sugarcane spirit.